Improving Beginning Numeracy Skills Using Number Stick Playing Strategies - Kustini; Basuki Hadi Prayogo; Pascalian Hadi Pradana; M. Agus Sugiarto (FKIP Universitas Halu Oleo, 2023)
The aim of the research is to improve children's initial numeracy skills through the strategy of playing with number sticks. The research was carried out at POS PAUD Flamboyan 60, Ledokombo District, Jember Regency. Children's numeracy skills, which are still lacking in terms of recognizing symbols or number symbols, need to be improved. Number stick games are used to improve children's basic numeracy skills. By using number sticks, children will help children recognize numbers visually. By seeing and holding number sticks, children can learn to identify and understand the sequence of numbers and can also be used to teach children how to count. This research uses a type of Classroom Action Research which consists of two cycles, consisting of three meetings in each cycle. This research activity takes the form of playing using number sticks by saying the numbers 1–10 in sequence correctly, grouping the numbers according to the teacher's instructions, so that children understand the concept of many and few, learn the concept of numbers, and count the number of digits that have been grouped. The results of the research show that using the strategy of playing with number sticks can improve children's initial numeracy skills. The results of this research can be shown by the criteria obtained which have developed very well in the five aspects observed in this research. The average value for cycle II was 84 and the average percentage increased, namely from before cycle to cycle I by 41% and from cycle I to cycle II by 31%.